Comparative Analysis of Inelastic Strain Recovery and Plastic Deformation in a Ti[49.1]Ni[50.9] (at %) Alloy under Torsion and Bending; AIP Conference Proceedings; Vol. 1683 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures - Grishkov V. N.; Lotkov A. I.; Baturin A. A. Anatoly Anatolievich; Timkin V. N.; Zhapova D. Yu. (2015, 2015)
Title screen